High‐Performance n‐Channel Organic Transistors Using High‐Molecular‐Weight Electron‐Deficient Copolymers and Amine‐Tailed Self‐Assembled Monolayers. Issue 13 (12th February 2018) - Wang, Yang; Hasegawa, Tsukasa; Matsumoto, Hidetoshi; Mori, Takehiko; Michinobu, Tsuyoshi
Abstract: While high‐performance p‐type semiconducting polymers are widely reported, their n‐type counterparts are still rare in terms of quantity and quality. Here, an improved Stille polymerization protocol using chlorobenzene as the solvent and palladium(0)/copper(I) as the catalyst is developed to synthesize high‐quality n‐type polymers with number‐average molecular weight up to 10 5 g mol −1 . Furthermore, by sp 2 ‐nitrogen atoms (sp 2 ‐N) substitution, three new n‐type polymers, namely, pBTTz, pPPT, and pSNT, are synthesized, and the effect of different sp 2 ‐N substitution positions on the device performances is studied for the first time. It is found that the incorporation of sp 2 ‐N into the acceptor units rather than the donor units results in superior crystalline microstructures and higher electron mobilities. Furthermore, an amine‐tailed self‐assembled monolayer (SAM) is smoothly formed on a Si/SiO2 substrate by a simple spin‐coating technique, which can facilitate the accumulation of electrons and lead to more perfect unipolar n‐type transistor performances. Therefore, a remarkably high unipolar electron mobility up to 5.35 cm 2 V −1 s −1 with a low threshold voltage (≈1 V) and high on/off current ratio of ≈10 7 is demonstrated for the pSNT‐based devices, which are among the highest values for unipolar n‐type semiconducting polymers. Abstract : High‐molecular‐weight ( M n ) n‐type semiconducting copolymers are synthesized via an improved Stille polymerization with Pd(0)/Cu(I) cocatalysts and chlorobenzene as the solvent. Due to the synergistic effects of the high M n, rational molecular design of sp 2 ‐nitrogen substitution, and an amine‐tailed self‐assembled monolayer, unipolar n‐channel organic transistors with remarkably high electron mobilities up to 5.35 cm 2 V −1 s −1 are achieved.